2007
DOI: 10.1136/jech.2006.055087
|View full text |Cite
|
Sign up to set email alerts
|

Population-based survey methods to quantify associations between human rights violations and health outcomes among internally displaced persons in eastern Burma

Abstract: Widespread human rights violations in conflict zones in eastern Burma are associated with significantly increased morbidity and mortality. Population-level associations can be quantified using standard epidemiological methods. This approach requires further validation and refinement elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 29 publications
7
85
2
Order By: Relevance
“…The estimated prevalence of Plasmodium falciparum malaria (6.9%) and under-5 diarrhea (10.3% in the previous 2 weeks) were comparable to a previous survey in Karen State (11.2% and 13.5%, respectively), though the estimate of moderate and severe malnutrition (14.8%) was higher (previously 4.2%) [5,8]. Maternal health indicators were poor, and were similar to those reported from selected clinic service areas participating in a reproductive health intervention study in 2008: only 17.1% of women of reproductive age met the international recommendation for consumption of iron supplements during pregnancy (previously 11.8%) [8], and nearly one fifth of women of reproductive age were found to be malnourished (16.7% in this study, 19.3% previously) [8].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The estimated prevalence of Plasmodium falciparum malaria (6.9%) and under-5 diarrhea (10.3% in the previous 2 weeks) were comparable to a previous survey in Karen State (11.2% and 13.5%, respectively), though the estimate of moderate and severe malnutrition (14.8%) was higher (previously 4.2%) [5,8]. Maternal health indicators were poor, and were similar to those reported from selected clinic service areas participating in a reproductive health intervention study in 2008: only 17.1% of women of reproductive age met the international recommendation for consumption of iron supplements during pregnancy (previously 11.8%) [8], and nearly one fifth of women of reproductive age were found to be malnourished (16.7% in this study, 19.3% previously) [8].…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, HRVs were associated with child malnutrition and an increased risk of death among infants, children and the population as a whole. Forced labor was most strongly associated with infant and child death; it was associated with a decreased risk of child malnutrition, a finding which has been reported elsewhere, though the reasons for this finding remain unclear and require further study [5]. However, many households that did not experience forced labor were exposed to other HRVs that also increase risk for malnutrition, such as forced displacement, thus making it possible that the "control" group in this instance had greater exposure to alternative, stronger risk factors for child malnutrition.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Studies around the world have found a correlation between human rights violations and adverse health outcomes [60,66]. By correlating health status to human rights violations during conflicts, researchers have provided evidence which can be useful to human rights monitors and humanitarian agencies and organizations [60].…”
Section: Human Rights Violationsmentioning
confidence: 99%